A comparison of approaches to the teaching and learning of science in Chinese and Australian elementary classrooms: cultural and socioeconomic complexities - Tao, Ying; Oliver, Mary; Venville, Grady (Wiley, 2013)
Set in the context of today’s globalized approaches to curriculum reform, the purpose of this study was to compare the teaching and learning of science in Chinese and Australian Grade 6 classrooms. A conceptual framework based on notions of culture and socioeconomic status informed the research design. Case study participants were three teachers of science and 140 students from three elementary schools of high, medium, and low socioeconomic status in Hunan Province, China; and three teachers and 105 students from paired schools in Western Australia. The formal curriculum, the curriculum-in-action, and the experiential curriculum in all case studies in each country were examined. Both qualitative and quantitative data were collected with student questionnaires, lesson observations, teacher interviews, a school tour, and document collection. Findings indicated that participating Chinese students reported a greater proportion of their science lessons involved activities such as reading textbooks and memorizing facts, activities that are consistent with Confucian educational culture. In Australia, where there has been a longer historical influence from social-constructivist theorists such as Bruner and Vygotsky, students reported their lessons involved a greater proportion of activities such as designing and doing science experiments, and working in small groups. The findings also indicated that in both countries, socioeconomic status was an important factor impacting the implementation of the science curriculum with students in higher socioeconomic status schools participating more frequently in classroom activities consistent with reform curriculum documents. This phenomenon was more apparent in China possibly due to the Confucian educational tradition supporting culturally viable alternative approaches to the teaching and learning of science.